Picture Exchange Communication System (PECS): A strategy to improve children’s speaking ability - Khoiriyah Khoiriyah (Universitas Ahmad Dahlan, 2020)
The implementation of Picture Exchange Communication System (PECS) strategy in this research aimed to improve children’s speaking ability. The indicators of speaking ability are child understands the meaning of the word used, able to connect the word to the denoted object, and to pronounce words understood by others. In other word, child is able to repeat sentences, ask questions with the correct sentence, and express opinions to others. This study uses qualitative method with the type of action research. The study was conducted in two cycles, with 3 meetings in each. The design of this study starts from the planning, implementation, observation, and reflection. The participants were 17 children aged 4-5 years old of group A1 TK ABA 4 Mangli Kaliwates Jember. The result showed that prior to PECS the children's speaking development rate was 17%, after the PECS action the speaking ability increased from 35% in the first cycle to 88% in second cycle. This shows that the speaking ability of early childhood can be improved with PECS approach.